Antimutagenicity and antioxidative DNA damage properties of oligomeric proanthocyanidins from Thai grape seeds in TK6 cells - Ratsada Praphasawat (2018)
Oligomeric proanthocyanidins (OPCs) are found mostly in red grape seeds. Many publications have reported that OPCs possess an excellent anti-oxidant effects. Since it could against cellular damage from reactive oxygen species (ROS) led to reduce the risk of chronic disease and cancers. We carried out this study on the Thai OPCs to evaluate the mutagenicity/anti-mutagenicity and anti-oxidative DNA damage effects in TK6 cells by micronucleus (MN) and comet assays. In the MN assay, OPCs-treatment of TK6 cells at concentrations ranging from 10-200 μg/ml (4 and 24 h) did not cause micronucleus induction over the negative control group but revealed a significant reduction the micronucleus frequencies against the known mutagen (mitomycin C). In the comet assay, OPCs-treated TK6 cells at concentrations of 100, 250, 500, and 1,000 μg/ml could inhibit DNA damage induced by H 2 O 2 as indicated by 18.7, 36.4, 30.6, and 60.1%, respectively. Our results suggest that OPCs possess the anti-mutagenic and anti-oxidative DNA damage effects in TK6 cells under the conditions of this assay.